REVISIÓN TAXONÓMICA DE LAS ESPECIES CHILENAS DEL GÉNERO A rth robrach u s SOLIER, 1849 (COLEOPTERA: MELYRIDAE) - EStrada M., Patricia; Solervicens A., Jaime (Acta Entomológica Chilena, 2022)
A taxonomic revisión of the chilean species o í Arthrobrachus is made. Through the study o f types 9 valid ñames and 17 synonymies are recognized: A. nigromaculatus Solier, 1849 (= scutellaris Phil. y Phil., 1864; =subaeneus Phil. y Phil., 1864; = nigromaculatus var. solieri Pie, 1919; =vicinus Pie, 1919; =impressithorax Pie, 1919); A. quadriguttalus Pie, 1919; A. rufitarsis Phil. y Phil. 1864 (=gennaini Pie, 1919; =minutus Pie, 1919); A.rufipennis Solier, 1849; A. tibialis Solier, 1849; A. maestus (Blanehard, 1843) (=quadripunctatus Phil. y Phil., 1864); A. Jlavipennis (Laporte, 1836) (= luteus (Blanehard, 1843); =varians Solier, 1849; =nigripenrtis Solier, 1849; =serratim argo Phil. y Phil., 1864; =puncticulatus Phil. y Phil. 1864;= tibialis var. inlineatus Pie, 1919); A. brasiliensis Pie, 190.3; A. limbatus Solier, 1849 (=ruficornis Phil. y Phil., 1864; =marginatus Phil. y Phil., 1864;= limbatus var. inlimbatus Pie, 1919). A new speeies is deseribed: A. latefasciatus n. sp. A new combination is established: Astylus subacuminatus (Solier, 1849) n. comb. A redescription o f the species using the male genital charaters is made. The distributional ranges o f every species is established and a key is provided.